Legal Protection of Business Actors from Payment Cancellation by E-Commerce Consumers Using a Cash-On-Delivery System - Rina Arum Prastyanti; Erma Rusdiana (West Science Law and Human Rights, 2023)
The purpose of this research is to describe the factors that cause business actors to be disadvantaged due to the COD system and protection for business actors against unilateral cancellation in the COD payment system. This research is a type of normative legal research that is descriptive in nature with a qualitative approach. The type of data used is secondary data. Secondary data is obtained from library materials that are relevant to the problems studied.  The data sources used are secondary data sources obtained from primary, secondary and tertiary legal materials. The data collection technique used is the study of documents or library materials.